Lubricating Effects Against Interfaces Shear Strength Of Soil–Concrete And Concrete–Concrete - Ardian Nor; Rustam Effendi (International Journal of Technology and Education Research, 2023)
Box Jacking is a trenchless method of underpass construction that consists in pushing one or more prefabricated concrete boxes into the soil using high capacity hydraulic jacks, while excavating the soil. The Box Jacking method generates soil-concrete frictions at all sides of a box and concrete-concrete friction while it is still on concrete platform. To minimalize this friction, lubricant such as oil and grease can be applied on all sides of the box. Objectives of this study are: 1) to identify soil classification, cohesion (c) and internal friction angle (f); 2) to obtain adhesion (ca) and interface friction angle (δ) for soil-concrete and concrete-concrete contact; 3) to obtain adhesion (ca) and interface friction angle (δ) for soil-concrete and concrete-concrete contact lubricated by oil; 4) to obtain adhesion (ca) and interface friction angle (δ) for soil-concrete and concrete-concrete contact lubricated by grease. Soil samples collected from soil investigation at Underpass Project Site at Tatakan, South Kalimantan, using soil boring test. Samples used for laboratory test are soil below 1.50-2.00 m, 2.50-3.00 m, and 4.50-5.00 m from ground surface. Cylindrical concrete samples are a diameter of 63.1 mm and a height of 20 mm. The concrete strength of concrete sample is 25 MPa. Lubricants used are oil and grease. Types of viscosity of oil used are SAE 5W-40, SAE 10W-40, SAE 15W-40, and SAE 20W-50. Type of viscosity of grease used are NLG#I, NLGI#2 and NLGI#3. Direct shear test was conducted to obtain soil-concrete and concrete-concrete friction values. Addition of grease to surface contact influences adhesion (ca) and interface friction angle (δ) significantly. In case of soil-concrete contact, adhesion (ca) and interface friction angle (δ) are 10.87 kPa and 22.64°. Addition of lubricant can decrease adhesion (ca) and interface friction angle (δ) to 11.80 kPa and 10.87° for oil and 0.44 kPa and 3.88° for grease. In case of concrete-concrete contact, adhesion (ca) and interface friction angle (δ) are 6.20 kPa and 32.93°. Addition of lubricant can decrease adhesion (ca) and interface friction angle (δ) to 4.26 kPa and 33.76° for oil and 0 kPa and 3.17° for grease.